Design electronic clock with azan reader and ringer / Ikhwan Mat Yasin @ Hashim and Kamaruzzaman Mat Rani - Mat Yasin @ Hashim, Ikhwan; Mat Rani, Kamaruzzaman (2005)
Using all the information we had, combining with the latest technology, we design a new digital clock with azan reader for the sake of completing this thesis. It is designed by using an IC 4701 that is combined with the software which we wrote in the personnel computer. Using this technique, the azan will ring from the computer every time a prayer time is entered. We only need to set it once, depending on where our country is, which latitude stays in, and what kind of azan reader we want to hear (from Mecca, Medina and many more). There are two type of azan, one for Subuh prayer, and the other one for another time (Zohor, Asar, Maghrib, and Isya’). But, we choose only the Penang period azan time to make our thesis simple and easy to manage and understand it operation. To set these prayer times, we need to program the software into PC by using Visual basics (VB) program. This type of clock can remind people especially who are always busy, to pray at the beginning of the prayer time. It can always remind us to Allah The Almighty and trained us to be a successful Muslim.